Analisis Persepsi Calon Guru terhadap Gaya Mengajar Otoriter di Sekolah Dasar: Antara Disiplin atau Ketakutan - Reni Reni; Jesi Alexander Alim; Zakiah Ulya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the perception of prospective teachers toward authoritarian teaching styles in elementary schools, focusing on two potential impacts: the formation of discipline and the emergence of fear in students. The research employs a descriptive qualitative approach using in-depth interviews with prospective elementary school teachers to explore their perceptions of the effectiveness and risks of authoritarian teaching styles in classroom management. Data were collected through direct interviews with 12 prospective teachers who shared their experiences, observations, and reflections on how this approach may influence student behavior and the learning environment. The findings reveal that prospective teachers view authoritarian teaching styles as effective in fostering discipline, order, and obedience among students. However, they also express concerns about the potential negative effects, such as fear, reduced student comfort, and limited participation in class activities. These perceptions highlight the need to balance discipline and psychological safety in elementary education, ensuring that teaching methods support both academic structure and emotional well-being.